The Role of the Islamic Students Association in Disseminating Islamic Values and Developing Education - Islahuddin, Islahuddin; Faiz, Muhammad; Nelwati, Sasmi (Khalifa Journal of Islamic Education, 2023)
This study examines the role of the Islamic Student Association in disseminating Islamic values, promoting a deeper understanding of religion, and improving the quality of education for students and the wider community. The research employs a qualitative method with a case study approach and involves seven informants from the second and third levels of cadre training. The findings show that the Islamic Student Association plays an important role in Islamic outreach activities and educational development. The organization contributes to strengthening the understanding of Islamic teachings and fostering critical awareness of various emerging social, political, and religious issues. Its outreach activities include public lectures, sermons, seminars, and group discussions that function as platforms for promoting Islamic values. In the field of education, the Islamic Student Association contributes through leadership training, academic mentoring, student self-development, and efforts to support the provision of higher-quality education. The findings highlight several implications, including the strengthening of organizational roles in Islamic outreach, the development of concept-based religious education, student empowerment, and character formation. This study provides a clearer understanding of the potential of the Islamic Student Association in the areas of Islamic outreach and education, and it may serve as a basis for enhancing the organization’s responsiveness to societal changes and community needs.